1990
DOI: 10.1161/01.hyp.15.2_suppl.i63
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive drugs distinctly modulate the rapid resetting of the baroreceptors.

Abstract: We investigated the distinct ability of various antihypertensive drugs to modulate the extent (%) of rapid (15 minutes) resetting of the baroreceptors of normotensive rats to hypertensive levels. In one protocol, hemorrhage produced a complete resetting to hypotension in rats chronically treated (6 days) with captopril. Also, hemorrhage produced only partial resetting in rats acutely treated (10-15 minutes before baroreceptor recording) with captopril and in control (untreated) rats (73±7% and 49±5%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Normotensive rats treated acutely with captopril, enalapril, or DuP 753 presented a slight but significant fall in MAP associated with a partial leftward curve shift and partial threshold shift to hypotensive levels. These data confirm previous observations from our laboratory, 7 based on changes of systolic pressure threshold for baroreceptor activation, that acute ACE inhibition with captopril facilitates rapid resetting to hypotensive levels. Nevertheless, the present study also demonstrates that acute ACE inhibition or blockade of Ang II receptors increases baroreceptor sensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Normotensive rats treated acutely with captopril, enalapril, or DuP 753 presented a slight but significant fall in MAP associated with a partial leftward curve shift and partial threshold shift to hypotensive levels. These data confirm previous observations from our laboratory, 7 based on changes of systolic pressure threshold for baroreceptor activation, that acute ACE inhibition with captopril facilitates rapid resetting to hypotensive levels. Nevertheless, the present study also demonstrates that acute ACE inhibition or blockade of Ang II receptors increases baroreceptor sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…5 Various antihypertensive drugs modulate rapid baroreceptor resetting to hypotensive levels, and among these, long-term (7-day) blockade of angiotensin II (Ang II) generation with captopril most efficiently modulates rapid resetting. 6 - 7 Vasoactive peptides such as Ang II also affect baroreceptor function. 8 - 10 Experiments in vitro in an aortic arch preparation 8 have demonstrated that as Ang II concentration increases, the pressurenerve activity curves shift in a parallel manner to higher pressures, requiring a substantially higher pressure threshold for baroreceptor activation.…”
mentioning
confidence: 99%
“…5 -7 On the other hand, recent investigations have demonstrated that various antihypertensive drugs including calcium antagonists and angiotensin-converting enzyme (ACE) inhibitors, which have become widely used in clinical practice, differently modulate acute resetting of the baroreceptors to hypotension. 8 - 9 We inferred, therefore, that various produced a leftward shift of the arterial pressure-aortic nerve activity relation to a similar extent (threshold pressure, 77±1 mm Hg, P<.Q5) in spontaneously hypertensive rats. In addition, treatment with the four agents equally augmented the maximum gain in spontaneously hypertensive rats (2.13±0.09% maximum/mm Hg, P<.05).…”
mentioning
confidence: 69%
“…elicited acute baroreceptor resetting. On the other hand, de Abreu and Salgado 9 reported that acute baroreceptor resetting induced by another calcium antagonist, nifedipine, was greater than that induced by hemorrhage. In vitro studies have also revealed conflicting results, suggesting that baroreceptor activity was affected 24 or not affected 25 by calcium antagonists.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation